Forest policy and politics in the Philippines the dynamics of participatory conservation - Contreras, Antonio P.; Leonen, Marvic M.V.F; Malayang, Ben S. III; Severino, Howie G.; Vitug, Marites Danguilan (Ateneo de Manila University Press, 2000)
'The essays in this collection originated under the auspices of an international research program on "Social and Political Dimensions of Environmental Protection Programs and Projects in Developing Countries" ... sponsored by the United Nations Research Institute for Social Development and supported financially by the Swiss National Science Foundation and the Swiss government's Agency for Development and Cooperation.' .. vii.